2015
DOI: 10.1371/journal.pone.0134484
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplex Label-Free Approach to Avian Influenza Surveillance and Serology

Abstract: Influenza serology has traditionally relied on techniques such as hemagglutination inhibition, microneutralization, and ELISA. These assays are complex, challenging to implement in a format allowing detection of several types of antibody-analyte interactions at once (multiplex), and troublesome to implement in the field. As an alternative, we have developed a hemagglutinin microarray on the Arrayed Imaging Reflectometry (AIR) platform. AIR provides sensitive, rapid, and label-free multiplex detection of target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Recently, researchers have started to develop protein microarrays for influenza virus serology. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 Protein microarrays are a high-throughput assay that can measure the magnitude and breadth of an antibody response. Like the ELISA (and unlike HI and MN assays), protein microarrays can also detect non-neutralizing antibodies, which are able to protect against influenza virus through effector functions such as antibody-dependent cell-mediated cytotoxicity and antibody-mediated cellular phagocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have started to develop protein microarrays for influenza virus serology. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 Protein microarrays are a high-throughput assay that can measure the magnitude and breadth of an antibody response. Like the ELISA (and unlike HI and MN assays), protein microarrays can also detect non-neutralizing antibodies, which are able to protect against influenza virus through effector functions such as antibody-dependent cell-mediated cytotoxicity and antibody-mediated cellular phagocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…7 With regard to influenza-targeted applications, we have demonstrated that multiplex hemagglutinin arrays have utility for rapidly assessing human serum samples for the presence of anti-influenza antibodies in a vaccine trial, 8 and provide a simple method for multiplex serology on avian surveillance samples. 9 Here, we provide a preliminary description of an AIR array intended to simplify the task of classifying newly observed strains of influenza, by enabling patterns of reactivity with the chip to be compared with those generated by known strains of the virus. In this manner, we anticipate that the lineage of the novel virus and its changes relative to known strains will be revealed.…”
Section: Bound Probementioning
confidence: 99%
“…Building on extensive previous work by multiple contributors in the field 15,16,17,18,19 , an influenza protein microarray was recently developed that contains over 250 purified hemagglutinin (HA) antigenic variants with representation of all 18 subtypes 12,20 . Using this methodology, a natural influenza infection was demonstrated to generate broadly reactive IgG and IgA antibodies against phylogenetically related HA subtypes, while an intramuscular influenza vaccination generated only subtype-specific IgG antibodies 21 .…”
Section: Introductionmentioning
confidence: 99%